Optical Properties of PVA/K2CrO4 Composite - Itab F. H. Al-Sulaimawi (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
The change in the optical properties for samples of pure PVA and PVA /K2CrO4composite have been studied .The samples were prepared with different percentage (1,3,5,and 7)%wt of K2CrO4 by casting method technique .In this work ,we are study the absorption ,reflectance spectra ,absorption  coefficient, energy gap ,extinction coefficient ,and transmittance spectra as a function of wavelength range (200-800)nm ,Also  real and imaginary part of dielectric constant have been studied in the range of wave length .The results exhibit the optical properties change by the increase of K2CrO4 concentration, and the values of energy gap for indirect transitions decrease by the increase of the concentration of  K2CrO4.